2016
DOI: 10.1371/journal.pone.0157662
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Processes and Drug Release: Capsaicinoids - Loaded Poly (ε-caprolactone) Microparticles

Abstract: We present a generalmodel based on fractional diffusion equation coupled with a kinetic equation through the boundary condition. It covers several scenarios that may be characterized by usual or anomalous diffusion or present relaxation processes on the surface with non-Debye characteristics. A particular case of this model is used to investigate the experimental data obtained from the drug release of the capsaicinoids-loaded Poly (ε-caprolactone) microparticles. These considerations lead us to a good agreemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…The drug delivery systems with a controlled and targeted release represent an alternative administration of a chili pepper extract. Lenzi et al 15 studied the diffusion process and the release of CAPs from poly(ε-caprolactone) microparticles; they obtained spherical particles that can deliver the CAPs rapidly to initiate the therapeutic effect, and the experimental release and diffusion profile were very similar to others estimated by Fick's law. Hydroxypropyl-beta-cyclodextrin, carboxymethyl-chitosansodium hydrogels, polyethylene glycol-polylactic-coglycolic acid thermosensitive hydrogel, flexible membrane vesicles, niosomal carriers, liposomes, and nanofibers were also developed as CAP carriers.…”
Section: Introductionmentioning
confidence: 65%
“…The drug delivery systems with a controlled and targeted release represent an alternative administration of a chili pepper extract. Lenzi et al 15 studied the diffusion process and the release of CAPs from poly(ε-caprolactone) microparticles; they obtained spherical particles that can deliver the CAPs rapidly to initiate the therapeutic effect, and the experimental release and diffusion profile were very similar to others estimated by Fick's law. Hydroxypropyl-beta-cyclodextrin, carboxymethyl-chitosansodium hydrogels, polyethylene glycol-polylactic-coglycolic acid thermosensitive hydrogel, flexible membrane vesicles, niosomal carriers, liposomes, and nanofibers were also developed as CAP carriers.…”
Section: Introductionmentioning
confidence: 65%
“…In this formula, the n value reports the type of physical phenomenon associated with the release. For delivery systems with spherical geometry, an n value less than 0.45 indicates that the release is controlled by diffusion (Fickian diffusion); an n value above 0.89 represents the drug release by polymer erosion (case II transport or non-Fickian transport mechanism); and an n value between 0.45 and 0.89 characterizes the anomalous transport with features of both mechanisms [53][54][55]58]. Taking all these into account, the formulation NC-1 showed an n value of 0.8816 by the Korsmeyer-Peppas model, which indicated that the physical mechanism of drug release from the TAC-loaded PCL occurred by the anomalous transport, in which the drug was released by the both Fickian diffusion and relaxation/polyester erosion as aforementioned [53].…”
Section: Model Equation Linear Equation R 2 Adjustedmentioning
confidence: 99%
“…Also, the fractional pharmacokinetics model has been used to avoid drug accumulation 25 . Moreover, Lenzi et al 26 have presented a distributed order fractional model to investigate the drug release profiles of the capsaicinoids-loaded poly microparticles. In addition to that, Kytariolos et al 27 present a methodology for power-law in vitro or in vivo (disorder media) by employing fractional calculus formalism.…”
Section: Introductionmentioning
confidence: 99%